2019
DOI: 10.22190/fume190330023k
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Indentor Sliding Velocity and Loading Repetition Factor on Shear Strain and Structure Dispersion in Nanostructuring Burnishing

Abstract: The article probes into a relationship of the shear strain intensity and the shear strain rate in the surface layer and the sliding velocity of a spherical indentor and its loading repetition factor. It brings forward an experimental procedure to evaluate the shear strain intensity and rate by analyzing the geometrical parameters of the bulge of plastically edged metal and the thickness of the shifted layer relative to different sliding velocities and feed rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…The refinement of the structure of the quenched AISI 420 steel by nanostructuring burnishing with a spherical indenter made of polycrystalline synthetic diamond was studied in [6]. It is shown that at a burnishing force of 340 N, a feed of 0.04 mm/rev, and with a change in sliding speed from 6 up to 26 m/min, the plastic shear deformation ranges from 2.1 to 3.4.…”
Section: Korzynski Et Al's Workmentioning
confidence: 99%
“…The refinement of the structure of the quenched AISI 420 steel by nanostructuring burnishing with a spherical indenter made of polycrystalline synthetic diamond was studied in [6]. It is shown that at a burnishing force of 340 N, a feed of 0.04 mm/rev, and with a change in sliding speed from 6 up to 26 m/min, the plastic shear deformation ranges from 2.1 to 3.4.…”
Section: Korzynski Et Al's Workmentioning
confidence: 99%
“…The primary problem is to create and improve the methods for finishing surface layer treatment of precision workpieces of tribo-couplings, providing hardening and high topographic properties of the surface layer. An effective method of finishing structural steels is the technology of nanostructuring burnishing, which makes it possible to form the nanostructured state and sub-microrelief of the surface layer during the precision workpiece serial manufacture at metalworking centers [6][7][8].…”
Section: Introductionmentioning
confidence: 99%